Assessment of liver size by ultrasonography. Issue 7 (17th March 2014) - Patzak, Monika; Porzner, Marc; Oeztuerk, Suemeyra; Mason, Richard Andrew; Wilhelm, Manfred; Graeter, Tilmann; Kratzer, Wolfgang; Haenle, Mark Martin; Akinli, Atilla Serif; the EMIL Study Group
ABSTRACT Background To determine liver span sonographically in a randomly selected population sample and identify factors that affect liver size. Methods A total of 1, 789 subjects (963 females, 826 males; mean age 41.8 ± 12.8 years) underwent sonographic examination of the liver in the midclavicular line to determine liver span. Subjects underwent physical examination and blood tests and completed a standardized interview questionnaire. Results The average liver span in the midclavicular line for the overall collective was 15.0 ± 1.5 cm; the average for females was 14.9 ± 1.6 cm and 15.1 ± 1.5 cm for males. Liver span exceeded 16 cm in 24.3% of subjects. Results of the multivariate analysis showed that, of the factors potentially influencing liver span, gender, age, body mass index, body height, fatty liver (p < 0.0001), waist‐to‐hip ratio (p = 0.015), and metabolic syndrome (p = 0.032) are significant. By contrast, diabetes mellitus, alcohol consumption, tobacco consumption, physical activity, and laboratory findings showed no influence. Conclusions Sonographic measurement of liver span in the midclavicular line is a simple method for routine clinical use. Gender, age, body mass index, waist‐to‐hip ratio, body height, hepatic steatosis, and metabolic syndrome are factors associated with liver span. © 2014 Wiley Periodicals, Inc. J Clin Ultrasound 42:399–404, 2014